Bioaccessibility and transformation of cadmium in different tissues of Zhikong scallops (Chlamys farreri) during in vitro gastrointestinal digestion. (15th February 2023) - Zhao, Yanfang; Wu, Jifa; Kang, Xuming; Ding, Haiyan; Sheng, Xiaofeng; Tan, Zhijun
Highlights: A significant organ-specific total cadmium distribution in Zhikong scallops ( Chlamys farreri ) The bioaccessibility of total Cd ranged from 44.0% (kidney) to 90.2% (gonad) for different tissues of C. farreri . Steaming decreased the total Cd bioaccessibility in the mantle, gill, gonad, digestive gland and muscle. The reactive cadmium ions (Cd 2+ ) could be detected in the digestive juice of five tissues except for the muscle. The bioaccessible Cd 2+ content in the digestive gland, gill and gonad tissues all significantly increased after steaming. Abstract: Scallop is well known for its high accumulation of cadmium. The bioaccessibility and speciation of cadmium in different tissues of scallops during gastrointestinal digestion could influence the evaluation of its biological effects and consumption safety in humans. The bioaccessibility of total Cd ranged from 44.0 % (kidney) to 90.2 % (gonad) for different tissues of scallop Chlamys farreri . Steaming decreased the total Cd bioaccessibility in the mantle, gill, gonad, digestive gland and the muscle. During in vitro digestion, the reactive inorganic Cd 2+ could be detected in the digestive juice of five tissues except for the muscle. Steaming process increased the bioaccessible Cd 2+ content for the digestive gland, gill and gonad tissues. Based on the bioaccessible total Cd and Cd 2+ content, the muscle, gonad, and mantle of the steamed scallops are the safe tissues for human consumption according to the scenarios of Cd intake established by WHO and EFSA.